Individual and synergistic influences of microstructural features on intergranular corrosion behavior in extra-low carbon type 304L austenitic stainless steel. (15th July 2018) - Pradhan, S.K.; Bhuyan, P.; Mandal, S.
Graphical abstract: Highlights: Coarse grained specimen suppress IGC by delaying onset/progression of sensitization. Residual strain accelerates sensitization leading to higher IGC and percolation. Large fraction of Σ3 n (n≤3) boundaries in GBE-specimen enhance the IGC resistance. GBE specimen shows better IGC resistance albeit presence of higher residual strain. GBCD has higher implication than grain size or residual strain in controlling IGC. Abstract: The individual and synergistic effects of the microstructural features viz. grain size, residual strain, grain boundary character distribution (GBCD) and its connectivity on intergranular corrosion (IGC) behavior is evaluated in type 304 L stainless steel. Straining accelerated sensitization by promoting chromium carbide precipitation via diffusion through dislocations. Coarse-grained microstructure suppresses IGC by delaying both the onset and progression of sensitization. Microstructure comprising of optimized GBCD exhibits remarkable resistance to IGC owing to the substitution of random high-angle boundaries by Σ3 and its variants. Impressively, evidences suggested that GBCD has higher implication than grain size or residual strain in controlling IGC behavior.